2014
DOI: 10.1158/1055-9965.epi-14-0146
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Platelet to Lymphocyte Ratio in Solid Tumors: A Systematic Review and Meta-Analysis

Abstract: Background: Inflammation influences cancer development and progression. An elevated platelet to lymphocyte ratio (PLR), a marker of inflammation, has been linked to poor prognosis in several malignancies. Here, we quantify the prognostic impact of this biomarker.Methods: A systematic review of databases was conducted to identify publications exploring the association of blood PLR and overall survival (OS) in solid tumors. Data were pooled in a meta-analysis. Pooled HRs for OS by disease group and by PLR cutoff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
600
6
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 640 publications
(635 citation statements)
references
References 49 publications
22
600
6
7
Order By: Relevance
“…In recently presented a meta-analysis, it was reported that a high NLR is associated with an adverse OS in many solid tumors (Templeton et al, 2014). This study showed no relationship between the pCR and pretreatment NLR values in locally advanced BC who received NACT.…”
Section: Discussionmentioning
confidence: 53%
“…In recently presented a meta-analysis, it was reported that a high NLR is associated with an adverse OS in many solid tumors (Templeton et al, 2014). This study showed no relationship between the pCR and pretreatment NLR values in locally advanced BC who received NACT.…”
Section: Discussionmentioning
confidence: 53%
“…Tumor cells possess the ability to manipulate platelet activity to optimize tumor growth, proliferation, survival and metastasis (29). Several studies have identified the association between a poor survival rate and elevated PLR in solid tumors (2,8,9,11,16,30). Szkandera et al revealed that an elevated PLR was significantly associated with a decreased time to recurrence and demonstrated a trend towards a decreased OS time in patients with stage II and III colon cancer that underwent curative resection (2).…”
Section: Stage IV ---------------------------------------------------mentioning
confidence: 99%
“…Recently, many studies have focused on hematological measurements or inflammatory factors, which are associated with the tumor microenvironment, for the diagnosis and prognosis of different cancers 6 . Previous clinical studies have confirmed that increases in the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio (PLR), neutrophil counts, or platelet counts were associated with negative clinical pathologic characteristics, such as a higher risk of recurrence, aggressive tumor biology, and greater disease progression, in patients with various types of cancer 7,8 . Platelets may release growth factors such as transforming growth factor b (TGF-b), platelet-derived growth factor (PDGF), and vascular endothelial growth factor (VEGF), which may contribute to the growth, progression, and metastasis of the tumor by stimulating the proliferation of ovarian tumor cells 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a reduced lymphocyte count is an indicator of a reduced immune response, and it is correlated with higher mortality in patients with OC than in healthy controls or patients with benign diseases 10 . The PLR, which is inexpensively and easily determined in routine clinical practice, was proposed to be a highly efficient and independent prognostic biomarker for many tumors 7 . Although there are several studies already published examining the relationship between PLR and cancer, the role of PLR in OC prognosis remains unclear 11 .…”
Section: Introductionmentioning
confidence: 99%